Blind spots in language textbooks. The issue of colonialism - Pogorzelska, Marzanna (Neofilolog, 2024)
The article presents the results of the analysis of over 80 English language textbooks published between 2000 and 2024. The aim of the study was to answer the question whether English textbooks contain elements of the discursive reproduction of colonialism as a practice of creating superior and subordinate identities, and what potential role textual absences and silence may play in this process. The study used the content analysis method with coding in the programme Atlas.ti and Critical Discourse Analysis to allow for qualitative examination of texts. As a result of the analysis, four main categories were distinguished which at the same time were dominant trends in textual references to colonialism(Colonization without the colonized, The colonized in a folklore trap, Invisibility of colonization, A different approach).The conclusions of the study show the textual absence of topics related to colonialism and the use of various types of silencing strategies to obfuscate the issue, whether in the form of backgrounding or exclusion of the colonized people, or by naturalizing the process of colonization itself. While critical research on textbooks, also in the context of blind spots, has had a long history, it has rarely focused on language textbooks, so the study aims to fill the gap in this area and contribute to further research.